Phenylalanine hydroxylase contributes to serotonin synthesis in mice. Issue 6 (16th May 2021) - Mordhorst, Alexander; Dhandapani, Priyavathi; Matthes, Susann; Mosienko, Valentina; Rothe, Michael; Todiras, Mihail; Self, Julie; Schunck, Wolf‐Hagen; Schütz, Anja; Bader, Michael; Alenina, Natalia
Abstract: Serotonin is an important signaling molecule in the periphery and in the brain. The hydroxylation of tryptophan is the first and rate‐limiting step of its synthesis. In most vertebrates, two enzymes have been described to catalyze this step, tryptophan hydroxylase (TPH) 1 and 2, with expression localized to peripheral and neuronal cells, respectively. However, animals lacking both TPH isoforms still exhibit about 10% of normal serotonin levels in the blood demanding an additional source of the monoamine. In this study, we provide evidence by the gain and loss of function approaches in in vitro and in vivo systems, including stable‐isotope tracing in mice, that phenylalanine hydroxylase (PAH) is a third TPH in mammals. PAH contributes to serotonin levels in the blood, and may be important as a local source of serotonin in organs in which no other TPHs are expressed, such as liver and kidney.